2021
DOI: 10.48550/arxiv.2108.11847
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A proper motion catalogue for the Milky Way's nuclear stellar disc

B. Shahzamanian,
R. Schoedel,
F. Nogueras-Lara
et al.

Abstract: We present the results of a large-scale proper motion study of the central ∼ 36 × 16 of the Milky Way, based on our high angular resolution GALACTICNUCLEUS survey (epoch 2015) combined with the HST Paschen-α survey (epoch 2008). Our catalogue contains roughly 80, 000 stars, an unprecedented kinematic data set for this region. We describe the data analysis and the preparation of the proper motion catalogue. We verify the catalogue by comparing our results with measurements from previous work and data. We provid… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 50 publications
4
6
0
Order By: Relevance
“…We tried doing this with one, two, and three-Gaussians models. To estimate the goodness of each fit, we used the logarithm of posterior probability, log Z (see Shahzamanian et al 2021). We found that the best fit is achieved with two Gaussians.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We tried doing this with one, two, and three-Gaussians models. To estimate the goodness of each fit, we used the logarithm of posterior probability, log Z (see Shahzamanian et al 2021). We found that the best fit is achieved with two Gaussians.…”
Section: Resultsmentioning
confidence: 99%
“…In the Galactic center, at a distance of ∼ 8 kpc (McNamara et al 2000;Ghez et al 2008;Genzel et al 2010), we can find the central molecular zone (CMZ), a flattened structure of gas and dust within a radius of ∼200 pc (Kruijssen et al 2014;Tress et al 2020). Occupying a similar space as the CMZ, there is the socalled nuclear stellar disk (NSD), a rotating structure (Schönrich et al 2015;Shahzamanian et al 2021), with a radius of ∼ 150 pc and a scale height of ∼ 45 pc (Launhardt et al 2002;Gallego-Cano et al 2020;Sormani et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NSD is rotating. The rotation of the NSD has been detected in APOGEE spectroscopic data by Schönrich et al (2015), in OH/IR and SiO maser stars by Lindqvist et al (1992) and Habing et al (2006), in ISAAC (VLT) near-infrared integral-field spectroscopy by Feldmeier et al (2014), in classical cepheids by Matsunaga et al (2015), in the KMOS spectroscopic survey by Fritz et al (2021), and in proper motions parallel to the Galactic plane by Shahzamanian et al (2021).…”
Section: Structure Of the Nsdmentioning
confidence: 90%
“…The 𝜇 𝑙 distributions of the NSD in the central fields show a characteristic double-peaked shape (Trippe et al 2008;Schödel et al 2009;Chatzopoulos et al 2015a;Shahzamanian et al 2021). This is due to rotation and can be understood by considering the limiting case of a cold disc of stars in purely circular motion: at 𝑙 = 0 stars move perpendicularly to the line-of-sight, and stars rotating in one sense (and placed in the front side of the NSD) will give rise to one peak, and stars rotating in the opposite sense (and placed on the back side of the NSD) to the other peak.…”
Section: Fiducial Modelmentioning
confidence: 99%